PERTUMBUHAN DAN HASIL DUA JENIS TANAMAN UBI BANGGAI (Dioscorea spp) PADA JARAK TANAM YANG BERBEDA - Indrianto Kadekoh,Nirwan Sahiri, Muh Sultan (AGROTEKBIS, 2016)
This study aimed to determine the growth and yield of two cultivars of Banggai (Dioscoreaspp) Yams at different planting space. This study used a Two Factorial Randomized Completely Block Design (RCB).Â The first factor was planting space (J) i.e. 100cm x50cm (J1), 100 cm x75cm (J2) and 100cmx100cm (J3). The second factor was the type of Banggai Yam (V1) consisted of Bakutuu (V1) and Baku Boan Memela (V2). The treatments were replicated three times resulting in18experimental units. The growth and yield of both yams were not significantly different under different planting spaces, but shoot number, tuber number and productivity of Â Bakutuu were higher than its counterpart.